Gizi Hormonal dan Kesehatan Reproduksi Remaja: Evaluasi Program Makan Gratis Berbasis Pemanfaatan - Josua, Dian Pertiwi; Nuridayanti, Nuridayanti; Irianti, Ruslina; Selang, Rustam AR; Sutisna, Anan; Suseno, Muchlas; Wijayanti, Retno (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: The free meal program (Makan Bergizi Gratis) in senior high schools aims to enhance student well-being by providing adequate nutritional intake. However, its implementation requires comprehensive evaluation, particularly regarding coordination mechanisms and the fulfillment of hormonal nutritional needs critical for adolescent development. This study analyzes the free meal program through the lens of the Utilization-Focused Evaluation (UFE) approach, with a specific focus on students' hormonal nutrition. Method: This research employed a mixed-methods design, combining qualitative descriptive analysis with a case study approach and quantitative anthropometric data. Qualitative data were collected through interviews and observations involving eight informants, including teachers and students. Data analysis involved data reduction, data display, and conclusion drawing, using both methodological and source triangulation to ensure data validity. Results: The findings indicate that: (1) Program coordination is suboptimal, with food delivery not consistently punctual. (2) The meals provided lack sufficient variety, particularly in delivering essential proteins and healthy fats necessary for hormonal balance during adolescence. (3) Student and parental involvement in menu selection and program evaluation remains limited. (4) Feedback to students is provided periodically. Implications: This study recommends strengthening inter-stakeholder coordination, diversifying the nutritional content of menus, and involving both students and parents in program evaluation. Sustainable funding is also identified as a critical factor for ensuring the program's long-term effectiveness. Novelty: This study offers novel insights into the application of Utilization-Focused Evaluation (UFE) in assessing free meal programs and highlights the importance of hormonal nutrition in supporting adolescent development.